Предмет: Алгебра,
автор: alkatras25625
(1-x^(2))^(2)+3,7(1-x^(2))+2,1=0
пжппжпжпжппжжппжжпжпжппжпжжпжпжпжпж
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(1-x²)²+3.7(1-x²)+2.1 = 0
1-x² = y
y²+3.7y+2.1 = 0
D = 3.7²-4*2.1 = 2.3²
y₁₋₂ = (-3.7±2.3)/2
y₁ = -3, y₂ = - 0.7
1-x² = -3
x²= 4
x₁ = -2, x₂ = 2
1-x² = -0,7
x² = 1.7
x₃= -√1.7
x₄ =
как-то вот тут некрасиво на мой взгляд
Похожие вопросы
Предмет: Русский язык,
автор: otamir99
Предмет: Русский язык,
автор: Дашуленька155
Предмет: Английский язык,
автор: irinafiber
Предмет: Математика,
автор: 1082сестры
Предмет: История,
автор: дианадиана6